In Silico Characterization of Lycopene Beta Cyclase (LCYB) and Lycopene Epsilon Cyclase (LCYE) Genes from DH-Pahang (Musa acuminata, A Genome) and DH-PKW (Musa balbisiana, B Genome): In Silico Characterization of LCYB and LCYE Genes - I Wiprayoga; Karlia Meitha; Fenny Dwivany (Journal of Tropical Life Science, 2023)
Alpha (α) and beta (β)-carotene are among the nutritious contents of bananas, with the unique feature of a high ratio of α-/β-carotene. Research on the gene and protein of the key enzymes determining the ratio of α-/β-carotene in bananas, namely lycopene beta cyclase (LCYB) and lycopene epsilon cyclase (LCYE), is currently not well defined. Hence, this study aimed to compare the characters of the LCYB and LCYE genes and their putative proteins from Musa acuminata 'DH-Pahang' and Musa balbisiana 'DH-PKW'. The corresponding nucleotide sequences from both species were aligned to detect similarities in the gene structure. Their protein products were characterized at the primary and tertiary levels. The phylogenetic tree was constructed based on nucleotide and protein sequences. The result showed that the gene structure between these two species is similar in LCYB in chromosome 9 but different in LCYB in chromosome 7 and LCYE. The presence of cis-acting regulatory elements in response to light dominated the 2000 nucleotide region of the 5'UTR of LCYB and LCYE genes in both species. Based on protein alignment and domain analysis, the NADB_Rossmann superfamily domain was detected in both LCYB and LCYE. Alignment of the three-dimensional protein structure showed a significant difference between MaLCYB.c07 and MbLCYB.c07 only. The phylogenetic tree based on protein sequences indicated the distant relationship of MaLCYB.c07 and MbLCYB.c07 with other LCYB ingroup OTUs. The results of this study could provide a molecular basis related to the exploration of bananas as a promising functional food to meet the needs of provitamin A.